Leprosy and Empire : A Medical and Cultural History - Edmond, Rod (Cambridge University Press, 2013)
This book ranges across several different parts of the imperial world and no one colonial terrain receives particularly detailed treatment. The metropolis remains a central point of reference, which might seem at odds with my ‘de-centring’ purpose. Certainly greater concentration on a single colonial territory would have allowed more detailed attention to indigenous understandings of leprosy. Jane Buckingham’s Leprosy in Colonial South India (2002) is an exemplary study of this kind.